Ethnobotanical study of medicinal plants in Ganta Afeshum District, Eastern Zone of Tigray, Northern Ethiopia - Leul Kidane; Gebrecherkos Gebremedhin; Tadesse Beyene (BMC, 2018)
Abstract Background Starting from the ancient time, the people of Ethiopia use medicinal plants as traditional medicine to heal different human and livestock ailments. This ethnobotanical study of medicinal plants was carried out in Ganta Afeshum District, Eastern Zone of Tigray, Northern Ethiopia, to identify medicinal plant species used by the local community to treat various human and livestock ailments. Methods A total of 78 informants (54 men and 24 women) were selected to collect ethnobotanical information from four study sites. Among the 78 informants, 20 key informants were selected purposefully; the other 58 informants were selected randomly by lottery method. Ethnobotanical data were collected using semi-structured interviews, field observations, guided field walks, and group discussions and were analyzed by preference ranking, paired comparison, direct matrix ranking, informant consensus factor, fidelity level (FL), use-value, independent samples t test, and Pearson correlation coefficients. Results A total of 173 medicinal plants were collected and identified that were distributed across 77 families and 156 genera. The family Fabaceae stood first by contributing 17 (9.8%) species followed by Lamiaceae and Solanaceae with 9 (5.2%) species each. Rhamnus prinoides was reported for the treatment of many of the described diseases. One hundred sixteen (67.1%) medicinal plant species were collected from natural vegetation, 34 (19.7) were from home gardens, 13 (7.5%) from farmland, and 10 (5.8%) were from natural vegetation and home gardens. The most widely used life form was herbs (69 species, 39.9%) followed by shrubs (58 species, 33.5%). The most commonly used part of the medicinal plants was the leaves followed by roots. The plants were prepared by grinding, powdering, squeezing, roasting, and burning and were administered through oral, dermal, nasal, anal, ocular, and vaginal, and on the surface of the teeth. The most commonly used applications were by drinking, smearing, eating, fumigation, and chewing. There was no difference between men and women informants, showing that the two sexes had similar knowledge in the use of traditional medicinal plants. Educational level and medicinal plant knowledge of informants were negatively correlated; whereas age and medicinal plant knowledge of informants were positively correlated. Conclusions Ganta Afeshum District is relatively rich in diversity of medicinal plant resources accompanied with a rich indigenous knowledge within the local communities to harvest and effectively use to prevent different human and livestock ailments. However, nowadays, deforestation, agricultural expansion, overgrazing, drought, and overexploitation are threatening these properties. Therefore, people of the study area should apply complementary conservation approaches (in situ and ex situ) for sustainable use of these resources and to prevent species extinction.